Assessing the Long Term Outcomes of Total Joint Replacement Surgeries Such as Hip or Knee Replacement (Medical Forum Monthly, 2023)
Objective: To assess the long term outcomes of total joint replacement surgeries such as hip or knee replacementStudy Design: cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Orthopaedic Surgery, Mardan Medical Complex from January 2021 to January 2023.Materials and Methods: Based on WHO sample size calculator, a total of 35 patients were enrolled in our study. All the patients were followed for a period of eighteen months. The range of motion, SF-36 score and Harris Hip Score VAS score was documented for all the patients pre-operatively. All the data analysis was done by using SPSS version 24.Results: In the current study, totally 35 patients were enrolled. In the total knee arthroplasty group, after following the patients for 18 months by employing the Knee Society Scoring system, the mean Knee score (SD) was 94.12 (±0.98) whereas the mean Functional score (SD) was 93.83 (±6.12). The mean preoperative and postoperative (SD) Range of Motion was 97.23 (±1.92) and 108.11 (±2.23) respectively. In the total hip replacement group, the mean post-operative function score (SD) was 35.66 (±6.31), mean SF-36 score (SD) was 68 (±4.11), mean post-operative pain score (SD) was 42.11 (±3.01) and the mean post-operative Harris hip score (SD) was 85.22 (±7.34) points.Conclusion: Our study concludes that all individuals demonstrated remarkable improvement in terms of the reduction of pain, range of movement, and abnormalities. All of the patients have adapted extremely well to the new way of life that is necessary following a complete hip or total knee replacement.